Total syntheses of ericifolione and its analogues via a biomimetic inverse-electron-demand Diels–Alder reaction. Issue 2 (8th December 2021) - Zhou, Tingting; Zheng, Anquan; Huo, Luqiong; Li, Changgeng; Tan, Haibo; Wang, Sasa; Chen, Huiyu
Abstract : A biomimetic tautomerization/intermolecular inverse-electron-demand hetero Diels–Alder reaction cascade to construct sterically hindered dihydropyran scaffolds was established and allowed the first total syntheses of ericifolione and analogues. Abstract : Driven by bioinspiration and appreciation of the structure of ericifolione, a biomimetic tautomerization/intermolecular inverse-electron-demand hetero Diels–Alder reaction cascade sequence promoted by sodium acetate to rapidly construct sterically hindered dihydropyran scaffolds was established, which allowed the first straightforward biomimetic total syntheses of ericifolione and its analogues with high simplicity. Moreover, this methodology set the stage for the preparation of relevant natural products or derivatives.